Afghan EFL students’ difficulties and strategies in learning and understanding English idioms - Sayeed Naqibullah Orfan (Cogent Arts & Humanities, 2020)
The study investigated the attitude of Afghan undergraduate EFL students towards the importance of learning English idioms, sources of difficulties in learning and understanding them, and strategies used to learn and understand idioms. It also explored the impact of students’ gender and first language on their responses. The data were collected from 337 students majoring in English language and literature through a questionnaire. SPSS version 26.0 was used to analyze the data. The results revealed that Afghan undergraduate EFL students had a very strong positive attitude towards the importance of learning idioms. The study also showed that EFL learners were aware of the difficulty of learning idioms. Their difficulties mainly came from lack of cultural knowledge behind idioms, lack of analogues for English idioms in their first language, and lack of context. Furthermore, students used numerous strategies to learn and understand idioms. Afghan EFL students’ gender and first language had no significant impact on their responses. The study recommends Afghan EFL instructors to incorporate idioms in their teaching activities.